2015
DOI: 10.1007/s11104-015-2526-1
|View full text |Cite
|
Sign up to set email alerts
|

Endophytes-assisted biocontrol: novel insights in ecology and the mode of action of Paenibacillus

Abstract: Background Biological control is an environmentally sound and effective means of reducing pathogeninduced damage to agriculture using natural antagonists. Paenibacillus is a cosmopolitan and ubiquitously occurring bacterial genus with antagonistic activity against phytopathogens. Many species and strains with promising potential for plant growth promotion and biocontrol of pathogens have been identified since Paenibacillus was first described 20 years ago. Nevertheless, important questions regarding the coloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(100 citation statements)
references
References 112 publications
4
95
1
Order By: Relevance
“…Regarding biocontrol, it is also worth mentioning that previous data on some genera can lead to new insights after using metadata analysis. Rybakova et al (2016b) reviewed the occurrence of Paenibacillus spp. in microbial metagenomes, as well as their occurrence as endophytes and the function of volatile organic compounds produced by members of this taxon.…”
Section: New Understanding Of Beneficial Bacterial Endophytes and Plamentioning
confidence: 99%
“…Regarding biocontrol, it is also worth mentioning that previous data on some genera can lead to new insights after using metadata analysis. Rybakova et al (2016b) reviewed the occurrence of Paenibacillus spp. in microbial metagenomes, as well as their occurrence as endophytes and the function of volatile organic compounds produced by members of this taxon.…”
Section: New Understanding Of Beneficial Bacterial Endophytes and Plamentioning
confidence: 99%
“…Biocontrol: Biocontrol refers to the eco-friendly way of reducing plant pathogens that may cause damage to agriculture crops through natural antagonists [39]. Most of the antagonistic rhizosphere bacteria are known biological control agents and belong to genera Bacillus and Pseudomonas.…”
Section: Indirectly Beneficial Mechanismsmentioning
confidence: 99%
“…Several endophytes cause ISR in plants against banana bunchy top virus [50]. Also, the common endophyte genus Paenibacillus is known to produce soluble and volatile metabolites that may inhibit the pathogen growth [39]. Moreover, endophytes protect plants from root pathogens by preparing biofilm around the roots [39].…”
Section: Biocontrol Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those volatiles 2,5-bis(1-methylethy)-pyrazine was produced. It was recently reported that Paenibacillus can produce pyrazines with broad spectrum antimicrobial activity against bacteria, fungi and yeast (Rybakova et al 2015). Here, the pyrazine-derivate was only detected for the bacterial mixture but not for Paenibacillus sp.…”
Section: Discussionmentioning
confidence: 66%